Analysis Of Football Dribbling Skills - Ades Fathu Fiyadinallah; Yusmawati; Wahyuningtyas Puspitorini (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
This research is motivated by the existence of various forms of soccer dribbling skill errors, namely first touch, coordination, and ball feeling as well as characteristic causes based on observations made by researchers, the facts in the field state that when the teacher delivers soccer dribbling material there are still many students who lack focus about understanding the strategy that the coach gives to students will have an impact on formations that cannot be applied during play. The next factor is that not many teachers/coaches apply various training models to the learning process, so it tends to be monotonous. The reason the author observes this problem is to find out, analyze and correct the form of football dribbling skills errors. The data collection method used in this research is a survey method with the locomotor skills test technique and the skill development phase test. The research sampling technique used a total sampling technique with a total of 40 responses from some class III and IV extracurricular students of Al-Fath BSD Elementary School, South Tangerang City. The research variables were basic first touch skills, coordination, and ball feeling in doing soccer dribbling. Analysis of research data using descriptive percentages. Based on the results of the assessment analysis, it can be concluded that the form of errors in the dribbling skills of the III and IV graders of football extracurricular is first touching 18%, coordination 45%, and ball feeling 15%. The cause of errors that occur in dribbling skills is a lack of coordination ability, this can be seen in the skill test percentage indicator after being analyzed.